Fundamentals of risk and insurance - Vaughan, Emmett J.; Vaughan, Therese M. (John Wiley & Sons, 2014)
"Fundamentals of Risk and Insurance, 11th Edition presents a thorough and comprehensive introduction to the field of insurance while emphasizing the consumer. The new edition first examines the concept of risk, the nature of the insurance device, and the rinciples of risk management. It then discusses the traditional fields of life and health insurance as solutions to the risks connected with the loss of income. Fundamentals of Risk and Insurance, 11th Edition alsodeals with the risks associated with the ownership of property and legal liability. "